Observations on the Portrayal of the Ruler in the Novels of Leo VI - Papagiannis, Grigorios; Tziatzi-Papagianni, Maria; Kollias, Vasileios-Alexandros; Nikolaou, Anastasia (Studia Ceranea, 2021)
The legal texts of the Byzantine period contain elements that clearly portray the role and duties of the emperor as ruler of the State. Leo VI the Wise (886–912 AD), famous for his abundant legislative and general legal work, promulgated numerous general laws (novels). His novels promote certain “ideals”, especially equality, justice, charity and clemency, along with other principles of Christian ethics. The emperor is illustrated as a ruler who has a close relationship with God, theologizes, and philosophizes at the same time. In parallel, the emperor infiltrates the mentality of his subjects as the one responsible for the people on earth, their tireless defender, and lawmaker. Furthermore, Leo appears to consistently try to accurately determine the most appropriate, prudent, and fair solution to each problem after meticulous study. He is a philanthropist, a lenient ruler and a supporter of equality and moderation. He acts as a protector of social institutions and regulates his subjects’ lives so that they can become more well-behaved and prefer only the useful things in life. Finally, in Leo’s novels the emperor is depicted not only as the person chosen by God to rule the Empire, but also as the true embodiment of justice, dignity and divine piety.